STUDY OF LIGHTNING ACTIVITY AND ESTIMATION OF LIGHTNING CHARACTERISTICS IN SARAWAK USING GENETIC ALGORITHM - JONG, FAR CHEN (Universiti Malaysia Sarawak (UNIMAS), 2018)
When lightning strikes to the transmission line, orifices in the insulation can be created. As a result, the insulation co-ordination between phases is breakdown and over-voltage will propagate across the transmission line in the form of electrical fields. Hence, the system will encounter under-frequency and prolonged type of destruction. In a worst-case situation, it may lead blackout. One of the effective ways to reduce lightning impact is to identify the lightning activity. This project has been carried out to familiarize the lightning activity in Sarawak area, hence the Genetic Algorithm (GA) has been utilized to optimize the crucial constants of the lightning empirical equation. As the constant values are successful to be optimized, estimation of Ground Flash Density (GFD) can be performed. However, the precisions of the results are under scrutiny, hence a lot of trials are required to be carried out in order to determine the best fitness value. In this project, there are three cases that had been carried out in determining the optimal solution in term of constant “a” and “b” for each sub-region in Sarawak. These results are presented and compared from the graph. In addition, this project has the potential to be discovered in further details for improvement